Modeling meso-scale-void formation during through-thickness flow in liquid composite molding - B. Yang; F. Y. Bi; S. L. Wang; C. Ma; S. B. Wang; S. Li (eXPRESS Polymer Letters)
Void formation during in-plane flow has been widely researched, while the void prediction method for throughthickness flow has not been reported, which restricts the effective quality control for through-thickness permeating type liquid composite molding (LCM). In this paper, the structural morphology and connectivity of mesopores in multi-layer woven fabrics have been studied, the difference between intra-yarn and inter-yarn flow paths during through-thickness permeating has been analyzed, and the air entrapment processes in different types of mesopores have been revealed. Based on the modeling of micro and meso through-thickness flow, a mathematical model to predict the formation and size of mesoscale-void has been established, the variation of intra-yarn flow path under different compaction conditions has been analyzed to guarantee the precision of the model. Experimental method has been designed to measure the size of meso-scale-void formed during through-thickness LCM, comparisons between prediction and experimental results have demonstrated the correctness of the above model.